2022
DOI: 10.3389/fmed.2021.796208
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Disparities in Quality of Life Among Older Adults From 1998 to 2018 in China: A National Observational Study

Abstract: ObjectiveTo investigate 20-year trends and disparities in quality of life among older adults in China from 1998 to 2018.MethodsOur study was based on eight representative nationwide health surveys among older adults conducted in China from 1998 to 2018. Quality of life data were obtained from 91,993 individuals aged 65 years or above. All surveys included identical indicators of self-reported quality of life, demographic factors, socioeconomic status, lifestyle habits, and health status. The trends in the stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…18 Other localized studies reached similar conclusions with the quality of life in these studies been measured by a single item rather than a validated scale. 19 , 20 Similar rural-urban HRQoL inequalities have also been observed in a longitudinal study tracking US veterans. 21 Although the urban-rural HRQoL difference have been compared, few research have went a closer looking at the differentials in urban-rural HRQoL influencing factors.…”
Section: Introductionsupporting
confidence: 64%
“…18 Other localized studies reached similar conclusions with the quality of life in these studies been measured by a single item rather than a validated scale. 19 , 20 Similar rural-urban HRQoL inequalities have also been observed in a longitudinal study tracking US veterans. 21 Although the urban-rural HRQoL difference have been compared, few research have went a closer looking at the differentials in urban-rural HRQoL influencing factors.…”
Section: Introductionsupporting
confidence: 64%
“…In older Brazilian community-dwelling adults, participants with 5 or more years of education tended to report better HRQoL (42). Household income was identified as a risk factor exacerbating the disparities in the prevalence of poor quality of life in a Chinese longitude study from 1998 to 2018 (22). The findings from Chen et al show that older adults' previous occupations played a role in affecting their HRQoL in mainland China (43).…”
Section: Discussionmentioning
confidence: 97%
“…In terms of the association between DD and HRQoL, it has also been confirmed by previous research. According to a 20year longitudinal study of 91,993 Chinese citizens over the age of 65, poor DD was significantly associated with a poor quality of life after being adjusted for potential confounders (22). Other cross-sectional and longitudinal studies have also identified that DD could benefit older adults' physical functional capacity (23) and memory status (24), as well as suppress cognitive impairment (25) and even mortality (26).…”
Section: Introductionmentioning
confidence: 99%